Experimental Investigation of Mixed Mode Forced Convection Solar Dryer for Turmeric (Curcuma Longa) - Husainy, Avesahemad S.N.; Pujari, Sunil; Wale, Gouri (Asian Review of Mechanical Engineering, 2018)
This paper presents an experimental effort on forced convection mixed mode solar dryer for turmeric at Miraj, India (16.83°N 74.63°E). To study the effect of drying time on mixed mode type forced convection solar dryer, 15kg of good quality of boiled turmeric are loaded. It has been experimentally analyzed that drying time can be reduced up to 7 days as compared to a conventional method which requires 13 – 15 days. The experiment was conducted in February month in Miraj, Maharashtra having incident solar radiation and wind speed 5.12 W/m2/day and 5 km/hr respectively. The drying experiment conducted with turmeric and it was found that the complete drying process could be attained with 47 hours (considering sunshine hr.) The effect of different air mass flow rate on moisture content, moisture ratio, drying rate, drying time and dryer efficiency has been evaluated for turmeric.